Lubricants and lubrication - Mang, Theo, ....-; Dresel, Wilfried, ....- (Weinheim : Wiley-VCH, 2001)
Contents: --------- 1. Lubricants and their market 2. Lubricants in the tribological system 3. Rheology of lubricants 4. Base oils 5. Synthetic Base oils 6. Additives 7. Lubricants in the environment 8. Disposal of used lubricating oils 9. Lubricants for internal combustion engines 10. Gear lubrication oils 11. Hydraulic oils 12. Compressor oils 13. Turbine oils 14. Metalworking fluids 15. Forming lubricants 16. Lubricating greases 17. Solid lubrication 18. Laboratory methods for testing lubricants 19. Mechanical-Dynamic testing methods for lubricants
Keywords: Smeermiddelen; Smering